The case for social evaluation in preverbal infants: gazing toward one’s goal drives infants’ preferences for Helpers over Hinderers in the hill paradigm - Hamlin, J. K. (Frontiers in Psychology, 2015)
In a 2007 empirical report, Hamlin, Wynn, and Bloom provided the first evidence that preverbal infants at 6 and at 10 months of age evaluate others on the basis of their helpful and unhelpful actions toward unknown third parties. In their “hill paradigm,” a Climber puppet tried but failed to climb a steep hill, and was alternately bumped up the hill by the Helper and bumped down the hill by the Hinderer. After being habituated to these events, both 10- and 6-month-olds selectively reached for the Helper over the Hinderer. In response, Scarf, Imuta, Colombo, & Hayne (2012b) provided evidence that rather than reflecting an early developing capacity for social evaluation, infants’ choices in Hamlin et al. reflected low-level perceptual preferences whereby infants are drawn to any character who is associated with the Climber bouncing. The current studies represent an attempt to adjudicate between the social and perceptual accounts of infants’ preferences for Helpers over Hinderers in the hill paradigm, by pitting a perceptual cue (e.g., bouncing) against a social cue (e.g., whether or not the Climber gazes toward his goal). Infants’ patterns of preference across 2 experiments support the social account.